Correlation of Muco-Cutaneous Lesions with Severity of Dengue Fever in Children - Varsha Suresh Ahirrao; Mohd Irfan Inamdar (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Infection by one dengue serotype provides lifelong immunity to that particular virus, but other serotypes have no cross protective immunity. Humans and mosquitoes are the principal hosts of Dengue virus; the mosquito remains infected for life but is known to cause illness only in humans. The virus transmitted by bites of Aedes mosquito. Subjects and Methods: Informed consent was taken from parents before enrolling in study. A clinical history, physical examination and relevant baseline investigations were done for all the cases. Patients were monitored for development of cutaneous and mucosal manifestations. A pre-structured proforma, which include demographic details of the patient, severity of illness, various mucosal and cutaneous manifestations and day of occurrence of the same, was used to record the clinical data and laboratory parameters from cases selected for the study. Results: Dengue fever was classified based on WHO guidelines 2012 into three categories, Dengue Fever without warning sign, Dengue Fever with warning sign and Severe Dengue. Out of 174 cases of Dengue Fever without warning Signs, 114 cases developed mucocutaneous manifestations i.e. 65.52%. Out of 89 cases of Dengue Fever with warning signs, 55 developed Mucocutaneous Manifestation ie 73.33% and out of 47 cases in Severe Dengue group, 42 cases developed Mucocutaneous Manifestations i.e. 89.36%. Conclusion: Mucoccutaneous Manifestations were more commonly seen in Severe Dengue compared to Dengue fever with warning signs and Dengue fever without warning signs which was statistically significant (p value < 0.05).